Customer Satisfaction as a Mediator of Experiential Marketing, Perceived Quality, and Perceived Value toward Customer Loyalty - Catur Setyo Nugroho; Arif Sudaryana; Guruh Ghifar Zalzalah; Latifah Putranti; Pradita Nindya Aryandha - (Journal of Business Management and Islamic Banking, 2025)
Research Aims: This study aims to analyze the influence of experiential marketing, perceived quality, and perceived value on customer satisfaction and customer loyalty at ROS IN Hotel, as well as to examine the mediating role of customer satisfaction in strengthening the relationship between these factors and customer loyalty.   Design/methodology/approach: This study used a quantitative causal design to examine the influence of experiential marketing, perceived quality, and perceived value on customer loyalty, with customer satisfaction as a mediating variable. Data were collected from 40 customers of ROS IN Hotel Yogyakarta using a purposive sampling method and a structured questionnaire on a five-point Likert scale. The data were tested for validity and reliability, then analyzed using path analysis.   Research Findings: The results show that only perceived value significantly influences customer loyalty, both directly and through customer satisfaction, while experiential marketing and perceived quality have no significant effects. This indicates that post-pandemic hotel customers prioritize functional value (price, convenience, safety) over emotional experiences or perceived service quality, with customer satisfaction acting as a key mediator.   Theoretical Contribution/Originality: This study identifies perceived value as the key driver of customer loyalty in the post-pandemic hospitality sector, showing that customers prioritize functional benefits over experiential or perceived quality, with customer satisfaction as a mediator. Research limitation and implication: This study, limited to customers of ROS IN Hotel Yogyakarta, implies that increasing perceived value is crucial for building satisfaction and loyalty, while enriching the theoretical understanding of post-pandemic customer behavior.